Contemporary Perspectives on Organizational Behaviour (IntechOpen, 2026)
Contemporary Perspectives on Organizational Behaviour explores leadership, organizational culture, and the future of business in a rapidly evolving world. This volume brings together diverse research and practical insights to examine how leadership styles influence workplace dynamics, the role of cultural competence in fostering collaboration, and the impact of dialogue on innovation. It highlights the importance of knowledge transfer across generations, the dynamics of teamwork in high-performance environments, and the behavioural traits that shape professional interactions. Beyond leadership and culture, the book delves into the changing business landscape, discussing stakeholder theory, ethical decision-making, and the adoption of circular economy principles for sustainable business models. It also explores how organizations adapt to digitalization and artificial intelligence, analyzing their transformative effects on decision-making, operational strategies, and structural change. By integrating interdisciplinary perspectives, this book provides a deep understanding of modern organizational challenges and effective strategies for navigating them. Designed for scholars, practitioners, and students alike, it offers valuable insights into leadership effectiveness, cultural adaptability, and long-term business sustainability. Whether you are an experienced professional, a future leader, or simply someone curious about how organizations work, this book gives you the tools to adapt, innovate, and succeed in a changing world.